Safari Dakwah PAI Sebagai Upaya Meningkatan Nilai Keislaman Pada Masyarakat Desa Sukamandi, Sagalaherang: Safari Dakwah PAI Sebagai Upaya Meningkatan Keislaman Pada Masyarakat Desa Sukamandi, Sagalaherang - Muhammad Nailul Author; Ahmad Zamakhsyari; Hadi Winarno; Muhammad Aiz; Wathroh Mursyidi; Eva Dwi Kumalasari; Nur Khuzaimah; Rafli Putra Rahman; Maulana; Meiliyanti Putri; Nabil (Yayasan Cerdas Pedia Indonesia, 2025)
The da'wah safari activity carried out in Sukamandi Village, Sagalaherang District, Subang Regency is part of the implementation of the Tri Dharma of Higher Education in the form of community service. The main objective of this activity is to provide a real contribution in the field of Islamic religious education that is appropriate to the needs and context of the community. This safari activity includes a deeper understanding of women's fiqh to the Al-Falah mothers' study group, practical basic fiqh learning such as prayer and thaharah with a nadzhom approach to students of SDN Sukamandi II, an introduction to the Ummi method for learning to read the Quran in more depth to children of MDTA Al-Falah, education about the concept of blessings for men at the Al-Falah Jamie Mosque. The implementation of this community service activity took place continuously for three days and received a very positive response from the local community. This activity showed an increase in knowledge, religious awareness, and the emergence of residents' desire to continue learning independently. In addition, this activity also demonstrated a form of real cooperation between students, lecturers, and the Sukamandi Village community in an effort to build a sustainable religious life.